Empowerment of Family Medicinal Plants (TOGA) as an Investment in Public Health in Sojomerto Village - Lilis Komala Dewi; Maliki Alfajr Davin Candra Saputra; Vivi Juli Pratiwi; Atia Mumtaza; Muhammad Hafiz Damanik; Nahnu Robid Jiwandono (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2024)
Can be planted in narrow land, TOGA (Family Medicinal Plant) or what is often called a live pharmacy can be one of the traditional solutions to keep public health when the flu and cough attack. Not only is it planting and caring for toga plants also tends to be easy. In this dedication the activities carried out are planting together with the villagers of Sojomerto while explaining the benefits of plants in the area. This planting is also intended as a medium of awareness related to land use, therefore activities are carried out in the land adjacent to the village hall in order to make it easier for citizens to care for, maintain and use plants.